2017
DOI: 10.18004/pdfce/2076-054x/2017.023(45)002-015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of potential health demands from changes in population dynamics in Paraguay

Abstract: Zavattiero, Fantin, Tornatore. Estimación de las potenciales demandas en salud a partir de los cambios en la dinámica demográfica en Paraguay 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…In a study carried out on potential health demands based on the demographic changes in Paraguay in 2017, it was found that 74.1% of the population did not have access to health services, among them 65.7% were from rural areas, and 87.4% from urban ones. 25 This result agrees with the one reported in this study, where 64% indicated not having access to private health services. It should be considered that the Paraguayan health system is made up of three paradigms, which are hospitalization, decentralization, and prevention; in turn, it consists of three systems: private, insurance for employed workers, and public health for the rest of the citizens.…”
Section: Discussionsupporting
confidence: 92%
“…In a study carried out on potential health demands based on the demographic changes in Paraguay in 2017, it was found that 74.1% of the population did not have access to health services, among them 65.7% were from rural areas, and 87.4% from urban ones. 25 This result agrees with the one reported in this study, where 64% indicated not having access to private health services. It should be considered that the Paraguayan health system is made up of three paradigms, which are hospitalization, decentralization, and prevention; in turn, it consists of three systems: private, insurance for employed workers, and public health for the rest of the citizens.…”
Section: Discussionsupporting
confidence: 92%